Traditional reindeer rangeland management and a (human) rights-based approach to food sovereignty - Harkoma, Assi; Forbes, Bruce C. (Routledge, 2020)
For decades, rapid, drastic changes in reindeer rangelands, also referred to as ‘pastures’ in Finland, have threatened the ability of the Sami to practice traditional reindeer herding and make their own decisions regarding reindeer husbandry. Depending on national reindeer herding legislation, this will have different effects in different parts of Sapmi, the traditional Sami areas in the northernmost parts of Norway, Sweden, and Finland and northwest Russia. This chapter will present a case study on declining pasture conditions and ‘overgrazing’ in the Finnish North. It will examine the potential of traditional pasture management and rotational grazing systems based on Indigenous knowledge (IK) to secure reindeer herding as a subsistence base for the production of healthy, culturally appropriate food through traditional food systems. This issue will be approached from a food sovereignty perspective by relating the Finnish Sami reindeer herders’ situation in relation to the six pillars of food sovereignty. This chapter will also discuss Finnish reindeer herders’ situation from a (human) rights-based approach. In brief, this analysis shows that a change towards more traditional rangeland management, supported by appropriate participatory modes of research that combine different ways of knowing about traditional grazing lands, collaborative decision-making processes, and adequate reindeer herding legislation, could be an important step towards increased food sovereignty in the Finnish parts of Sapmi.